Peptide Toxin Diversity and a Novel Antimicrobial Peptide from the Spider Oxyopes forcipiformis - Kexin Wang; James Mwangi; Kaixun Cao; Yi Wang; Jinai Gao; Min Yang; Brenda B. Michira; Qiumin Lu; Juan Li (Toxins)
Spider venoms are emerging as a rich source of bioactive peptide toxins with therapeutic potential. Lynx spiders of the genus Oxyopes are small, cursorial hunters that employ complex venom to subdue arthropod prey. However, extracting crude venom from these diminutive arachnids poses significant challenges. This study presents a transcriptome analysis of venom glands from an undescribed Oxyopes forcipiformis species, revealing 339 putative protein and peptide toxin sequences categorized into seven functional groups. The venom composition was dominated by membrane-active peptides (40.71%), venom auxiliary proteins (22.71%), neurotoxins (15.63%), channel active peptides (7.08%) and uncharacterized components (13.87%). Additionally, phylogenetic analysis of 65 disulfide-bond-rich peptides yielded six distinct families based on sequence homology and cysteine framework. Finally, a novel antimicrobial peptide, GK37, was identified using in silico and homology analyses. Our data suggested that GK37 presented significant antibacterial activity against Gram-positive bacteria Staphylococcus aureus with a minimum inhibitory concentration (MIC) of 1.552 µM by disrupting bacterial membranes. At 4× MICs, GK37 almost showed no hemolytic activity on blood cells or toxicity against Hek293T cells. Our findings provided a basis for targeted studies of the diversity and pharmacological effects of lynx spider peptide. We elucidated a valuable high-throughput approach for obtaining proteins and peptides from small-group spiders.